2014
DOI: 10.2337/dc13-1904
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Consequences of Diabetic Ketoacidosis at Initial Presentation of Type 1 Diabetes in a Prospective Cohort Study of Children

Abstract: OBJECTIVETo investigate the impact of new-onset diabetic ketoacidosis (DKA) during childhood on brain morphology and function.RESEARCH DESIGN AND METHODSPatients aged 6–18 years with and without DKA at diagnosis were studied at four time points: <48 h, 5 days, 28 days, and 6 months postdiagnosis. Patients underwent magnetic resonance imaging (MRI) and spectroscopy with cognitive assessment at each time point. Relationships between clinical characteristics at presentation and MRI and neurologic outcomes were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
191
0
11

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(208 citation statements)
references
References 36 publications
6
191
0
11
Order By: Relevance
“…Several studies have also shown that diabetes associated ketoacidosis can cause cerebral edema, hemorrhagic stroke, or acute ischemia leading to intracerebral complications [16,17]. Recent studies using MRI measures show altered brain structure and injury associated with adverse neurocognitive outcomes including impairment in neuronal function and viability in T1D children [18,19]. Ketosis mediated cerebrovascular endothelial dysfunction has been shown to be associated with intracranial microvascular complications [20].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have also shown that diabetes associated ketoacidosis can cause cerebral edema, hemorrhagic stroke, or acute ischemia leading to intracerebral complications [16,17]. Recent studies using MRI measures show altered brain structure and injury associated with adverse neurocognitive outcomes including impairment in neuronal function and viability in T1D children [18,19]. Ketosis mediated cerebrovascular endothelial dysfunction has been shown to be associated with intracranial microvascular complications [20].…”
Section: Introductionmentioning
confidence: 99%
“…Later in life, declines in FA are associated with progression of aging in healthy populations (22). Alterations in FA have been seen in patients with T1DM (23,24), and alterations in MD have been associated with diabetes complications (25). Thus, in addition to functional ICN strength, measures of FA and MD can provide additional information on the structural alterations that may coincide with altered ICN activity.…”
Section: Introductionmentioning
confidence: 99%
“…In world terms, the occurrence of T1DM in children is expressive and its incidence has been increasing around 3% per year (2)(3)(4)(5)(6) . This disease can present long-term complications, and is the cause of high morbidity and mortality with impacts on the quality of life and increasing healthcare costs requiring interdisciplinary interventions, comprehensive care, health education, monitoring/follow-up checkups, surveillance, and rational and efficient use of available technologies (7)(8) .…”
Section: Introductionmentioning
confidence: 99%
“…Access to services and integration of health care are also fundamental and constitute challenges for organizing health care for these children, being common situations in the Brazilian reality (5)(6)9) . In Primary Health Care (PHC), basic actions for the child focus on monitoring growth and development, immunization, breastfeeding, healthy eating, accident prevention and attention to diseases prevalent during childhood, taking into consideration that family participation and partnership with health and community services are essential (10)(11) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation